2022
DOI: 10.1039/d2py00739h
|View full text |Cite
|
Sign up to set email alerts
|

High temperature shape memory poly(amide-imide)s with strong mechanical robustness

Abstract: Shape memory polymers (SMPs) show tremendous application prospect in various fields owing to their stimuli responsiveness. However, their application in high value-added aerospace still remains a great challenge, since it...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…These tensile properties are significantly higher than those of a majority of reported polyimines whose tensile strength is typically in the range of 20–50 MPa with tensile modulus less than 1.5 GPa, ,,,,,,, and are even comparable to those of some traditional high-performance polyimides (tensile strength: 90–120 MPa, tensile modulus: 2–3 GPa). , On the one hand, the prepared PIIH films contain rigid and large polar imide linkages (Figure S39, Supporting Information), which increases the polymer backbone rigidity and the intermolecular interactions as well as the cohesive energy density, thus endowing the resulting PIIH films with high tensile modulus and tensile strength. On the other hand, the as-synthesized bisimide-containing diamines possess flexible ether linkages, and the cross-linker, tri­(2-aminoethyl) amine, also contains elastic methylene units (Figure S39, Supporting Information), which could facilitate the single bond rotation and conformational rearrangement of the polymer network when subjected to external stress, consequently increasing the toughness and robustness of the PIIH networks. ,,,, By contrast, when o -MHBIDA and m -3FBIDA are used to fabricate polyimines, the tensile strength slightly decreases to 88.3 MPa for o -MPIIH and 83.6 MPa for m -3FPIIH . However, an evident reduction in tensile properties is observed for Un -PIIH (tensile strength 71.5% of that of o -DMPIIH and tensile modulus 63.3% of that of o -DMPIIH ) when all substituents are eliminated from the starting diamine monomer Un -HBIDA .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These tensile properties are significantly higher than those of a majority of reported polyimines whose tensile strength is typically in the range of 20–50 MPa with tensile modulus less than 1.5 GPa, ,,,,,,, and are even comparable to those of some traditional high-performance polyimides (tensile strength: 90–120 MPa, tensile modulus: 2–3 GPa). , On the one hand, the prepared PIIH films contain rigid and large polar imide linkages (Figure S39, Supporting Information), which increases the polymer backbone rigidity and the intermolecular interactions as well as the cohesive energy density, thus endowing the resulting PIIH films with high tensile modulus and tensile strength. On the other hand, the as-synthesized bisimide-containing diamines possess flexible ether linkages, and the cross-linker, tri­(2-aminoethyl) amine, also contains elastic methylene units (Figure S39, Supporting Information), which could facilitate the single bond rotation and conformational rearrangement of the polymer network when subjected to external stress, consequently increasing the toughness and robustness of the PIIH networks. ,,,, By contrast, when o -MHBIDA and m -3FBIDA are used to fabricate polyimines, the tensile strength slightly decreases to 88.3 MPa for o -MPIIH and 83.6 MPa for m -3FPIIH . However, an evident reduction in tensile properties is observed for Un -PIIH (tensile strength 71.5% of that of o -DMPIIH and tensile modulus 63.3% of that of o -DMPIIH ) when all substituents are eliminated from the starting diamine monomer Un -HBIDA .…”
Section: Resultsmentioning
confidence: 95%
“…On the basis of the stress relaxation time ( τ ), which is defined as the time required to relax 1/ e (∼63%) of the initial stress according to the Maxwell model, T v and the activation energy ( E a ) for imine bond exchange are calculated according to the reported literature (Figures S42–S46; see the Supporting Information for calculation details), ,, as is listed in Table . It is clearly indicated that T v of the prepared PIIH s (33.8–144.0 °C) is much lower than their T g (211–306 °C), and the calculated E a (except Un -PIIH ) is much higher than that of a few reported polyimines whose E a is typically in the range of 40–80 kJ/mol. , According to Leibler’s topology transition theory, , in the case of T v lower than T g , even if the temperature (less than T g ) is higher than T v , the thermodynamic condition for bond exchange reaction is satisfied, but because the polymer network is frozen, the bond exchange reaction is actually restricted and thus the topology rearrangement cannot proceed, which is experimentally evidenced by the slight stress relaxation at 80 °C depicted in Figure f for Un -PIIH , whose T v is as low as 33.8 °C. However, once the temperature reaches close to T g , the imine bond exchange reaction is aroused and all samples exhibit rapid stress relaxation with τ decreasing from a few minutes to several seconds, and thorough stress relaxation can be achieved.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…T g variation of PI films with different NTPA content is mainly due to amide H-bonding and the rigid pyridine ring structure of NTPA. Amide linkage induces interchain Hbonding, 49 and pyridine ring 50,51 that helps to increase the rigidity of polymer chain, which combine to stiffen the polymers. As a result, higher content of NTPA leads to higher T g of co-PI films.…”
Section: Mechanical and Thermal Properties Of Co-pismentioning
confidence: 99%
“…In the application process, SMPs usually serve in different temperature environments 25 . The variation behavior of the mechanical properties of SMPs with temperature change determines whether or not they can perform their function 26,27 . To guarantee the safety and structural reliability of SMPs at extreme temperatures, it is critical to reasonably modeling the TDTS and analyzing the strength influencing factors.…”
Section: Introductionmentioning
confidence: 99%